Moth Swarm Algorithm for Solving Combined Economic and Emission Dispatch Problem - Jevtic, Milena; Jovanovic, Nenad; Radosavljevic, Jordan; Klimenta, Dardan (Elektronika ir Elektrotechnika, 2017)
In this paper, the Moth Swarm Algorithm (MSA) is applied to the Combined Economic and Emission Dispatch (CEED) problem in thermal power plants. The analysis of behavior and the evaluation of performances of the algorithm are carried out on the standard test systems with 3 and 6 generators. The results of the MSA application to these test systems are compared with the results published in recent literature. The present paper shows that the proposed MSA gives an accurate and effective solution of the CEED problem. DOI: http://dx.doi.org/10.5755/j01.eie.23.5.19267